Sex dimorphism in the associations of gestational diabetes with cord blood adiponectin and retinol-binding protein 4 - Hua He; Wen-Juan Wang; Guang-Hui Zhang; Meng-Nan Yang; Huei-Chen Chiu; Dan-Li Zhang; Qinwen Du (BMJ Open Diabetes Research & Care, 2020)
Introduction Gestational diabetes (GD) is associated with impaired insulin sensitivity in newborns. Adiponectin and retinol-binding protein 4 (RBP-4) are involved in regulating insulin sensitivity. Females are more likely to develop diabetes at young ages than males. We tested the hypothesis that GD may affect RBP-4 and adiponectin levels in early life, and there may be sex-dimorphic associations.Research design and methods In a nested case–control study of 153 matched pairs of neonates of mothers with GD and euglycemic pregnancies in the Shanghai Birth Cohort, we evaluated cord plasma leptin, high molecular weight (HMW) and total adiponectin and RBP-4 concentrations.Results Comparing GD versus euglycemic pregnancies adjusted for maternal and neonatal characteristics in female newborns, cord plasma total adiponectin (mean±SD: 30.8±14.3 vs 37.1±16.1 µg/mL, p=0.048) and HMW adiponectin (14.6±7.7 vs 19.3±8.3 µg/mL, p=0.004) concentrations were lower, while RBP-4 concentrations were higher (21.7±5.4 vs 20.0±4.8 µg/mL, p=0.007). In contrast, there were no differences in male newborns (all p>0.2). RBP-4 concentrations were higher in female versus male newborns (21.7±5.4 vs 18.8±4.5 µg/mL, p<0.001) in GD pregnancies only. HMW adiponectin concentrations were significantly higher in female versus male newborns in euglycemic pregnancies only (19.3±8.3 vs 16.1±7.4 µg/mL, p=0.014).Conclusions GD was associated with lower cord plasma HMW adiponectin and higher RBP-4 concentrations in female newborns only. The study is the first to reveal a sex-dimorphic early life impact of GD on metabolic health biomarkers in the offspring. GD may alter the normal presence (HMW adiponectin) or absence (RBP-4) of sex dimorphism in some insulin sensitivity regulation-relevant adipokines in early life.